PEMBUDAYAAN PENDIDIKAN INDONESIA (Sebuah Tuntutan Perubahan Peradaban Bangsa) - Yulius Rustam Effendi (STIPAS St. Sirilus Ruteng, 2014)
Themost voluptuous BREAKTHROUGH at century21 happened notonly because of the technology, but also because of the growth of the concept about what is the meaning of becoming a human being.The Existence of human being deals always with a rich “ posibility